Continuous Flow Synthesis of Secondary Amides by Tandem Azidation– Amidation of Anilines - Spiteri, Christian; Moses, John E. (Synlett, 2012)
The continuous flow synthesis of a variety of secondary amides by tandem azidation–amidation of anilines is described. This new procedure benefits from the improved safety feature of generating aromatic azides in flow, thus ensuring low concentrations of any potentially hazardous intermediates. The protocol was amenable to the production of multi-gram quantities of the amide product.
Keywords: flow chemistry; amide synthesis; aromatic azides; azidation–amidation; synthetic methods